Moon Phase as the Cause of Monday Irrationality: Case of Asean Day of the Week Anomaly - Brahmana, Rayenda Khresna; Chee, Wooi Hooy; Zamri, Ahmad (University of Bucharest, 2014)
Many Day-of-the week anomaly papers have suggested investor behaviour as the explanation of highly differentiated returns on Mondays; yet, rarely found a paper has empirically investigated it. Therefore, this paper proposes Moon-Induced mood as the determinant of that irrational behaviour. This proposition is based on our preliminary findings that the full moon phase occurred more often on Mondays compared to other days; an indication of a causal relationship. By taking Indonesia, Malaysia, Thailand, and the Philippines as samples during the period of 1999-2010, this paper found: (1) There is evidence of a Monday effect across all the ASEAN stock markets, (2) The moon phase and its interaction with Mondays has significantly influenced the Monday effect, and (3) A full moon on Monday has significant negative influenced on Monday returns. In conclusion, the stimulation by moon phase forms affection bias, and the resulting outcome is the irrational stock market behavior.